INFORMATION DISCLOSURE ABOUT INVESTMENT PROPERTY IN THE FINANCIAL STATEMENTS ACCORDING TO INTERNATIONAL STANDARDS (Economics and region, 2017)
UDC 657 Valentyna Dubovaya, PhD (Economics), Associate Professor. Iryna Davydova, student. Poltava National Technical Yurii Kondratiuk University. Information Disclosure about Investment Property in the Financial Statements According to International Standards. The purpose of the research is elaboration of a structured form for information disclosure of investment property in the financial statements in accordance with international standards. According to the results of research it was elucidated, that as opposed to global trends of excessive information disclosure, the financial statements of Ukrainian enterprises in accordance with IFRS has insufficient, and sometimes non-significant, financial information disclosure, at least concerning investment property. For the structured information disclosure about the investment property in the Notes to the financial statements in accordance with IFRS it was proposed an ordered presentation of descriptive and financial information with using the tabular forms of reconciliation of the carrying value of investment property at the beginning and end of the reporting period according to the alternative models of evaluation. It was defined the prospects of subsequent research of application of international accounting approach to the investment property evaluation at fair value with taking into account her best and more profitable using.Keywords: IFRS, information disclosure, investment property, notes to the financial statements.